(untitled) (Nomico, 2025)
The mawah (profit and loss sharing) system in Acehnese society seems to have been abandoned because it is considered unable to compete with the sophisticated and modern global economic system. In fact, mawah is substantively a populist economy that helps the lower middle class to play an active role in the economic sector while still providing mutual benefits for capital owners (shahibul mal) and capital managers (mudharib). In addition, the practice of usury through loan sharks is increasingly phenomenal in Acehnese society. Therefore, research on economic empowerment with the mawah system in the context of Acehnese local wisdom is very important to do. The purpose of this study is to reveal the economic empowerment of the community with the mawah system in the socio-cultural context and find the implications of mawah in economic empowerment with a socio-cultural approach. Qualitative research with data tracking techniques through observation, interviews and documentation in two locations, namely Aceh Tamiang and Pidie Jaya. The results of the study revealed economic empowerment with a local wisdom approach through the mawah system is still practiced in Acehnese society based on the principles of brotherhood, ta’awun(mutual help), amanah (credible), responsibility and honesty which are preceded by an oral agreement with a profit-loss sharing pattern. While the implication is that the mawah system can improve work ethics and productive efforts so that it can support and increase the income of family economists.